Misalignment effects on isotropic roughness hydrodynamic finite journal bearings - Che Hassan Che Haron, (1993)
Hydrodynamically lubricated isotropic roughness bearing with the misalignment of the journal is analysed. A modified Reynolds' equation which includes surface roughness and misalignment effects is solved numerically using finite difference method with the aid of successive-over-relaxation method. The average flow model is employed in evaluating hydrodynamic pressure due to isotropic roughness and misalignment effects. The bearings' characteristics' values is solved numerically using Simpson's rule. The results of the numerical analysis explore the effects of both surface roughness and misalignment on the design parameter of journal bearing. The degree of misalignment and roughness structure greatly effects the performance of the hydrodynamic bearings. Controlling the roughness and degree of misalignment is an important design factor particularly for bearings operating at minimum film thickness and high eccentricity ratio